The Role of Graduate Attributes on Student Success in the Higher Institution of Learning: A Case Study of Durban University of Technology, South Africa - Ncube , Thandukwazi Richman; Matlala, Mpubane Emanuel (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
Graduate attributes have received significant attention in recent years as the higher institutions of learning seek to renew and articulate their tenacities. Though many claims are made with respect to the implementation of graduate attributes, there is emergent acceptance of the proposition that the strongest evidence of their achievement is their explicit embedding in assessment. The higher institutions have always endeavoured to develop desirable qualities in their graduates. However, for many students, this has been an implicit rather than explicit consequence of their university experience as the development of graduate attributes has traditionally been considered so fundamentally inherent to all teaching and learning as to warrant no further special attention. The study examined the influence of graduate attributes on student success in Durban University of Technology. The population consisted of Public Relation Management programme. The results indicated that there is a vast amount of significant relationship between graduates attributes and student success. The overall findings of the study provided evidence that graduate skills and attributes relate positively to general employability of industry sector. Therefore, the study recommended that there must be a constant need for collaboration between the higher institutions and the industry to ensure curriculum is developed in a way that it can serve both the need of employer/industry partner and the need of the student in order to transform and acquire the adequate graduate attributes suitable for employment.